Air gasification of agricultural waste in a fluidized bed gasifier: hydrogen production performance - Wan Ab. Karim Ghani, Wan Azlina; Moghadam, Reza Alipour; Mohd Salleh, Mohamad Amran; Alias, Azil Bahari (MDPI, 2009)
Recently, hydrogen production from biomass has become an attractive technology for power generation. The main objective pursued in this work is to investigate the hydrogen production potential from agricultural wastes (coconut coir and palm kernel shell) by applying the air gasification technique. An experimental study was conducted using a bench-scale fluidized bed gasifier with 60 mm diameter and 425 mm height. During the experiments, the fuel properties and the effects of operating parameters such as gasification temperatures (700 to 900°C), fluidization ratio (2 to 3.33 m/s), static bed height (10 to 30 mm) and equivalence ratio (0.16 to 0.46) were studied. It was concluded that substantial amounts of hydrogen gas (up to 67 mol%) could be produced utilizing agricultural residues such as coconut and palm kernel shell by applying this fluidization technique. For both samples, the rise of temperature till 900°C favored further hydrocarbon reactions and allowed an increase of almost 67 mol% in the release of hydrogen. However, other parameters such as fluidizing velocity and feed load showed only minor effects on hydrogen yield. In conclusion, agricultural waste can be assumed as an alternative renewable energy source to the fossil fuels, and the environmental pollution originating from the disposal of agricultural residues can be partially reduced.